Modal Sosial dan Mekanisme Adaptasi Masyarakat Pedesaan dalam Pengelolaan dan Pembangunan Infrastruktur - Kusumastuti, Ayu (Masyarakat: Jurnal Sosiologi, 2015)
This research tried to explore bonding social capital which could be transformed to rural society adaptive capacity of infrastructure development. The adaptive capacity of society has an elastic power, flexibility, and stability in society if they can mobilize resource and modify social institution. The research conducted in Sidoasri Village, Sumbermanjing District, Malang County. This research utilized case study as qualitative approach. Data collecting used in-depth interview, and observation. The society has been developing water, electricity, road infrastructure since they has trust, strong interaction, and norm among the community members. It indicated the type of bonding social capital. This exclusive social capital has been yielding cooperation, participation, appropriate technology utilization, mutual exchanges, and mobilization of collective action. Forms of adaptive capacity which have been developed are an elastic power and flexibility to maintain rural infrastructure development.